Upper Campanian – Lower Maastrichtian pachydiscus from the Penderisco Formation, Western Cordillera (Antioquia – Colombia) (2014)
Cretaceous ammonoids from Colombia have been studied extensively. However, only a few records have been reported from the Western Cordillera so far. Here, we reported the occurrence of Pachydiscus (P.) cf. flexuosus near to the Giraldo village in the Antionquia Province (Colombia). The paleontological material was recovered during an extensive geological survey carried on around the towns of Santa Fé de Antioquia and Cañasgordas. The single specimen recovered was found in a calcareous concretion located in situ at the base of the Penderisco Formation. This new biostratigraphic data suggest an upper Campanian to lower Maastrichtian range for the lowest part of the Penderisco Formation in the area.